(3efGbH GdEeGe eGdcs - (3CHheOjf TYjH Hf YHO Gdg Hf YHO GdcGaj GdeUQj GdTgjQ HGdMQjajTs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdhe ddYde fSHkG, hGZfGge Hg hEf YOehG eGdkG hfSHkG (B[(3cPG(B] s
(3BNQgG (B:s
(3GfJgi ef cJGH GdQhV GdaGFb aj GdehGYX hGdQbGFb HdaXg hUdi Gddg Yi SjOfG eMeO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B323 - (3U(B334s
(3ef GdQhV GdaGFb aj GdehGYX hGdQbGFbs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs